PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA CARD GAME TERHADAP PENGETAHUAN DAN SIKAP TENTANG KONSUMSI JAJANAN SEHAT DI SDN 005 SAMARINDA SEBERANG - Muri’ah Firda Nurul’ain; Dian Ardyanti; Bernadetha Bernadetha (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Introduction: Diarrhea is a disease caused by not consuming healthy snacks so that various diseases start to appear, for example stomach ache, toothache, and the worst thing is diarrhea. Objective: To determine the influence of health education using card game media on knowledge and attitudes regarding the consumption of healthy snacks at SDN 0005 Samarinda Seberang. Method: This research is a quantitative research using the Pre Experiment method, research design using a One Group Pre test and Post test design, with a sample size of 64 students at SDN 005 Samarinda Seberang. Sampling used simple random sampling. Results: Data analysis through statistical tests followed by the Wilcoxon test. The results of data analysis for the Experimental group given the card game media intervention had a significant effect on knowledge P = 0.000 (p<0.05) and attitude P = 0.000 (p,0.05). Card game media has an influence on increasing students' knowledge and attitudes about consuming healthy snacks at SDN 005 Samarinda Seberang. Conclusion: This research can be used as an alternative choice of health education media in conveying information about consuming healthy snacks and can be used as a literature source in developing further research.